Climate Change Impacts on Water Resources and Adaptation in the Rural Water Supply and Sanitation Sector in Nicaragua - World Bank (2014)
Climate change is at the top of the development agenda in Central America. This region, together with the Caribbean, is highly vulnerable to the effects of climate change in Latin America. Climate change is manifesting itself through higher average temperatures and more frequent droughts that result in higher water stress, and through the rising frequency of extreme weather events such as tropical storms, hurricanes, floods and landslides, all of which pose significant challenges in the rural water supply and sanitation sector. The paper starts with a review of the historic data on temperature and precipitation trends in Central America and particularly at the regional level in Nicaragua. The data reveal a clear trend of the growing climate variability, increased water stress for crops, and greater frequency of extreme weather events. The rising intensity and frequency of ex-treme weather events is among the most critical risks to the region's development agenda, and they translate into high economic losses. This paper examines the impacts and implications of potential climate change on water resources in Nicaragua and makes key recommendations to integrate climate change and rural water supply and sanitation policies and programs in a way that increase resilience to current and future climate conditions.